(untitled) (The International Journal for Scientific Research, 2024)
The analytical study of the development of vehicle insurance in the Kingdom of Saudi Arabia addresses the importance of insurance in Saudi society and its impact on the economy and social development. The study begins by highlighting the Industrial Revolution and the development of the global economy, and how this led to an increase in the number of vehicles and an increasing need for insurance. The study shows that insurance has become an indispensable social necessity due to the huge number of factories and economic companies in the Kingdom of Saudi Arabia. Insurance works to compensate for damages and disasters to which individuals are exposed, and represents solidarity and support in society. The study indicates that insurance companies provide different types of insurance that meet the needs of individuals and companies. It also points to the close relationship between economic growth and the growth of the insurance sector, as the development of the economy contributes to supporting the sector and increasing its investments. The study concludes with the importance of developing the insurance sector in the Kingdom of Saudi Arabia and improving the services provided, in addition to enhancing awareness of the importance of insurance and motivating citizens to benefit from insurance services to protect their property and enhance financial and social stability in the country.